Leadership based on Path-Goal Theory of School Administrators and Job Motivation of Teachers under Vocational Education in the Three Southern Border Provinces - Kama , Bustaman; Kao-ian, Jarunee; Waichompu, Navarat (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2022)
The purpose of this research was to study and compare the relationship between leadership based on Path-Goal theory of school administrators and job motivation of teachers under vocational education in the three southern border provinces. The samples of this research were 260 people. The research instrument was a five-level rating scale questionnaire with an IOC of .60 or higher and a reliability of .98. The data were analyzed using statistics; frequency, percentage, mean, standard deviation, t-test, F-test, pair-wise comparison test by Scheffe method and Pearson’s Correlation. The research results showed that school administrators had leadership based on Path-Goal theory in all aspects at a high level. The overall work motivation of teachers was at a high level. The hypothesis test results indicated that differences in gender, age and education background had no difference in leadership based on Path-Goal theory. However, teachers receiving different types of experience had difference in work motivation with a statistical significance at .05. In addition, it was found that the overall relationship between leadership based on Path-Goal theory of school administrators and job motivation of teachers showed positive correlation at a high level with a statistical significance at .01.